FDA Approval Summary: Ruxolitinib for Treatment of Steroid‐Refractory Acute Graft‐Versus‐Host Disease. (22nd October 2019) - Przepiorka, Donna; Luo, Lola; Subramaniam, Sriram; Qiu, Junshan; Gudi, Ramadevi; Cunningham, Lea C.; Nie, Lei; Leong, Ruby; Ma, Lian; Sheth, Christopher; Deisseroth, Albert; Goldberg, Kirsten B.; et al.
Abstract: On May 24, 2019, the Food and Drug Administration approved ruxolitinib for steroid‐refractory acute graft‐versus‐host disease (SR‐aGVHD) in adult and pediatric patients 12 years and older. Approval was based on Study INCB 18424‐271 (REACH‐1; NCT02953678), an open‐label, single‐arm, multicenter trial that included 49 patients with grades 2–4 SR‐aGVHD occurring after allogeneic hematopoietic stem cell transplantation. Ruxolitinib was administered at 5 mg twice daily, with dose increases to 10 mg twice daily permitted after 3 days in the absence of toxicity. The Day‐28 overall response rate was 57.1% (95% confidence interval [CI]: 42.2–71.2). The median duration of response was 0.5 months (95% CI: 0.3–2.7), and the median time from Day‐28 response to either death or need for new therapy for acute GVHD was 5.7 months (95% CI: 2.2 to not estimable). Common adverse reactions included anemia, thrombocytopenia, neutropenia, infections, edema, bleeding, and elevated transaminases. Ruxolitinib is the first drug approved for treatment of SR‐aGVHD. Implications for Practice: Ruxolitinib is the first Food and Drug Administration–approved treatment for steroid‐refractory acute graft‐versus‐host disease in adult and pediatric patients 12 years and older. Its approval provides a treatment option for the 60% of those patients who do not respond to steroid therapy. Abstract : Ruxolitinib is the first FDA‐approved treatment for steroid‐refractory acute graft‐versus‐host disease. This article provides a summary of the FDA review of ruxolitinib, based on the REACH‐1 Study.